Drosophila WASH is required for integrin-mediated cell adhesion, cell motility and lysosomal neutralization. - Nagel, B.M.; Bechtold, M.; Rodriguez, L.G.; Bogdan, S. (Journal of Cell Science, 2017)
The Wiskott-Aldrich syndrome protein and SCAR homolog (WASH; also known as Washout in flies) is a conserved actin-nucleation-promoting factor controlling Arp2/3 complex activity in endosomal sorting and recycling. Previous studies have identified WASH as an essential regulator in Drosophila development. Here, we show that homozygous wash mutant flies are viable and fertile. We demonstrate that Drosophila WASH has conserved functions in integrin receptor recycling and lysosome neutralization. WASH generates actin patches on endosomes and lysosomes, thereby mediating both aforementioned functions. Consistently, loss of WASH function results in cell spreading and cell migration defects of macrophages, and an increased lysosomal acidification that affects efficient phagocytic and autophagic clearance. WASH physically interacts with the vacuolar (V)-ATPase subunit Vha55 that is crucial to establish and maintain lysosome acidification. As a consequence, starved flies that lack WASH function show a dramatic increase in acidic autolysosomes, causing a reduced lifespan. Thus, our data highlight a conserved role for WASH in the endocytic sorting and recycling of membrane proteins, such as integrins and the V-ATPase, that increase the likelihood of survival under nutrient deprivation.